Syncope: An Atypical Presentation of Pulmonary Embolism Secondary to Occult Uterine Malignancy. (12th July 2018) - Qutrio Baloch, Zulfiqar; Ayyaz, Muhammad; Hussain, Muhammad; Abbas, Shabber Agha; Samreen, FNU
Abstract : All syncopal patients who present to the emergency department should be considered for pulmonary embolism (PE) as part of their differential diagnosis. PE presenting as a syncopal episode and associated with occult uterine malignancy is uncommon. Review of the literature indicates that up to 10% of patients with unprovoked venous thromboembolism (VTE) are diagnosed with cancer in the year following that first episode of VTE. In patients suspected of having a PE who do not manifest any source of an embolism require eventual workup to screen for an occult malignancy. Here, we report a 74-year-old female who presented to the emergency department following an unexplained sudden loss of consciousness and eventually was found to have a massive saddle embolus caused by a uterine malignancy-induced VTE.